An interaction index to predict turtle bycatch in a Mediterranean bottom trawl fishery. (January 2016) - Lucchetti, Alessandro; Pulcinella, Jacopo; Angelini, Valeria; Pari, Sauro; Russo, Tommaso; Cataudella, Stefano
Abstract: Incidental catch is the major threat to the survival of loggerhead turtles ( Caretta caretta ) in the Mediterranean and the main reason for their decline. More than 100, 000 turtles are estimated to be caught annually due to fishing practices; 10–50% die. Bottom trawls are among the fishing gears exerting the worst impact on sea turtle populations, especially in the coastal waters of Tunisia and Libya, northern Adriatic Sea, the Mediterranean coastal areas of Turkey and Egypt, where the continental shelf is large and turtles in the demersal stage are commonly found also in winter. Seven adult-sized loggerhead turtles captured incidentally by bottom trawls in the central-northern Adriatic Sea and treated in rescue centres were tagged with satellite transmitters before release. In this paper Italian bottom trawl track data obtained from vessel monitoring systems (VMSs) were analysed by VMSbase R suite to identify the areas of maximum fishing effort in the Adriatic. These data were combined with satellite information on turtle distribution to provide an interaction index enabling prediction of potential trawl–turtle interaction hotspots and periods. The present pilot study can be considered as a risk-analysis approach directed at identifying the areas and times of possible trawling–turtle interactions in a Mediterranean trawl fishery. By identifying the areas and seasons at highest risk of turtle bycatch, the index here developed has the potential to provide key information to design and implement mitigation strategies. Vessel monitoring system is actually in force in several countries, therefore the approach here studied might have a worldwide application.